Cosmopolitismo y decadentismo en la literatura latinoamericana. Rama (re)lee a Martí junto a Rimbaud - Josiowicz, Alejandra (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
.- The article explores the idea of internationalisation of Latin American culture in the end of the XIXth. century in the last essays of Ángel Rama on José Martí. Its main thesis is that Rama`s Latinoamericanism suffers a great shift by the consideration of international culture, particularly, the influence of European culture, in the modernists: French decadents, on one side, English intellectuals, Oscar Wilde and physist John Tyndall, on the other side, and also the restoration of Hispanic tradition. The emphasis in the relationship with the French poet Rimbaud opposes the official image of José Martí by depicting him as a “maudit” and a “malade”. Portraying maybe the most representative Latin American poet as culturally fable and characterized by a tortuous subjectivity, the essay “José Martí en el eje de la modernización poética…” not only implies a change in the idea of Latin America but also signifies a modernization in cultural criticism. The article holds a dynamic conception of space and time together with the opening of a creative intercultural connection between the Americas and Europe. It draws a ryzomatic space between transatlantic cultural territories, characterized by a non- linear interchange of influences.